The Impact of Corporate Diversification on Firm Performance. - Lizares, R. M.
This study investigates the relationship between corporate diversification and firm performance of Philippine publicly-listed non-financial firms, using the resource-based view (RBV) view of the firm as its framework. The results show that the: (1) degree of diversification has a positive effect on firm performance; and (2) type (related or unrelated) of diversification has different effects on firm performance, with related diversification outperforming unrelated diversification. Ultimately, firm performance is linked to the successful diversification of valuable, rare, and inimitable economies of scope to related businesses, and not just to the absolute amount of diversification.
Keywords: Management -- Periodicals; Diversification; Firm Performance; Resource-Based View (RBV).; Rumelt measure